2020
DOI: 10.3390/agronomy10091436
|View full text |Cite
|
Sign up to set email alerts
|

Crambe: Seed Yield and Quality in Response to Nitrogen and Sulfur—A Case Study in Northeastern Poland

Abstract: The aim of this study was to determine the effect of nitrogen (0, 30, 60, 90, 120 kg ha−1) and sulfur (0, 15, and 30 kg ha−1) fertilization on the morphometric parameters of plants, seed yield components, seed and straw yield, N fertilizer use efficiency (NFUE), and quality of crambe seeds. The experiment had a randomized complete block design, and it was carried out in Bałcyny (northeastern Poland) in 2017–2019. In northeastern Poland, the average seed yields ranged from 0.96 to 1.64–1.82 Mg ha−1 (hulled seed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 85 publications
4
13
1
Order By: Relevance
“…as 116 plants/m 2 , and the average YPP as 2.5 g. Arslan et al [20] reported TSW values between 2.6 and 8.5 g and YPP values of 0.8-5.1 g/plant for 82 C. abyssinica genotypes. Nevertheless, in the wild Crambe species in this study, there were approximately 4.5 plants/m 2 , and the average YPP was 125.5 g. The PR, determined as 22.7% for C. orientalis and 22.3% for C. tataria in this study, had values similar to those reported by Sokolski et al [21] as 20.8-23.8% in the culture form of Crambe (Crambe abyssinica Hochst. ex RE Fries).…”
Section: Discussionsupporting
confidence: 87%
“…as 116 plants/m 2 , and the average YPP as 2.5 g. Arslan et al [20] reported TSW values between 2.6 and 8.5 g and YPP values of 0.8-5.1 g/plant for 82 C. abyssinica genotypes. Nevertheless, in the wild Crambe species in this study, there were approximately 4.5 plants/m 2 , and the average YPP was 125.5 g. The PR, determined as 22.7% for C. orientalis and 22.3% for C. tataria in this study, had values similar to those reported by Sokolski et al [21] as 20.8-23.8% in the culture form of Crambe (Crambe abyssinica Hochst. ex RE Fries).…”
Section: Discussionsupporting
confidence: 87%
“…7), demonstrating that crambe preferred environments with higher temperatures and precipitation concentrated in single events rather than spread along the cycle. Seed yield in Poland (1.73 Mg ha -1 DM) is similar to values observed by Sokólski et al (2020), and slightly higher than those found by Krzyżaniak and Stolarski (2019), who reported a maximum value of 1.51 Mg ha -1 DM in large scale trials (>1 ha). Crambe seed yields in Italy (grand mean 2.11 Mg ha -1 DM) are considerably higher than those previously reported by Laghetti et al (1995), possibly due to improved genetics of Galactica compared with older accessions.…”
Section: Discussionsupporting
confidence: 81%
“…Despite growing interest by the biobased industry, crambe cultivation has never taken off in Europe, and only sporadically worldwide. Crambe oil is characterized by high compositional stability (Sokólski et al, 2020), and so has great potential as an ideal feedstock for the biobased industry. In the present study, this quality trait of crambe was confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…Mineral fertilization usually leads to an increase in the concentrations of NDF and ADF in the seeds of winter oilseed rape [26,29] and other Brassica crops [7,36]. In the present study, only the NDF content of seeds was significantly affected by fertilization (Table 2).…”
Section: Fiber Fractionsmentioning
confidence: 41%